Kontribusi Ekonomi Perempuan Penjual Ayam Goreng Gerobak di Beberapa Pasar Satelit di Kota Padang - Yuzaria, Dwi; Fitrini, Fitrini (Fakultas Peternakan Universitas Jambi, 2010)
Increased socio-economic demands has elevated the complexity of family needs. To fulfill all these needs, women should participate in making a living. This study aimed to look at the economic performance of women in small business, particularly in-cart-fried-chicken business; identify the constraints faced and provide an alternative to overcome the constraints. The study was conducted by survey method with respondents of in-cart-fried-chicken seller on some market centers in Padang city. The sample is determined by proportional allocation of 15 people, meanshile the data were analyzed using descriptive analysis method. The results of research is that the economic performance of women in this business is quite low with 5.07 working hours per day. Approximately 32.5% of all those business- women participate in all activities from planning to marketing. This business is potential enough to be developed, with an average income level of USD 92,259.58 per day and approximately 1.29 R/C ratio. Internal constraints faced by these women is the pattern of relations in the family that marginalize women's role in meeting the economic needs of families, while the external constraint is the difficulty to seek additional capital for business development and fluctuations in the price of chicken as main raw material. An alternative that can be offered is to open a branch business at home for women to devote more time, and access to soft loans which apply an unheavy terms. The conclusion of the research was that women had roles in making a living for the family, however, the role is low because there were patriarchi values as internal constraints and capital as the main external constraint. The solution is to find for a soft loan and establish good relationships with suppliers of raw materials.